2021
DOI: 10.3390/medicina57111197
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Clinical Outcomes in Patients with Fragility Fractures of the Lumbar Spine, Thoracic Spine, and Pelvic Ring: A Comparison of Data before and after Certification as a DGU® Geriatric Trauma Centre

Abstract: Background and Objectives: The implementation of orthogeriatric co-management (OGCM) reflects the demand for interdisciplinary collaborations due to the increasing comorbidities of geriatric trauma patients. This study aimed to assess clinical in-hospital outcomes in lumbar spine, thoracic spine, and pelvic ring fragility fracture patients before and after the implementation of a Geriatric Trauma Centre (GTC) certified by the German Trauma Society (DGU®). Materials and Methods: In this observational, retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…As collaborative orthogeriatric care was initially intended for hip fractures, most studies focused on these fractures and found beneficial effects compared to usual care regarding in-hospital [ 10 , 13 , 14 ], 30-day [ 15 21 ], and 1-year mortality [ 10 , 14 , 18 , 22 24 ], regain of functional status and walking ability [ 13 , 24 , 25 ], and more quality-adjusted life years [ 22 , 26 ]. Studies focusing on pelvic and spine fractures found benefits compared to usual care in terms of more identified complications [ 27 , 28 ] and fewer revision surgeries necessary [ 28 ]. However, evidence on mortality for fracture sites other than hip or outcomes for humerus and forearm fractures is less conclusive or lacking at all [ 27 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As collaborative orthogeriatric care was initially intended for hip fractures, most studies focused on these fractures and found beneficial effects compared to usual care regarding in-hospital [ 10 , 13 , 14 ], 30-day [ 15 21 ], and 1-year mortality [ 10 , 14 , 18 , 22 24 ], regain of functional status and walking ability [ 13 , 24 , 25 ], and more quality-adjusted life years [ 22 , 26 ]. Studies focusing on pelvic and spine fractures found benefits compared to usual care in terms of more identified complications [ 27 , 28 ] and fewer revision surgeries necessary [ 28 ]. However, evidence on mortality for fracture sites other than hip or outcomes for humerus and forearm fractures is less conclusive or lacking at all [ 27 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on pelvic and spine fractures found benefits compared to usual care in terms of more identified complications [ 27 , 28 ] and fewer revision surgeries necessary [ 28 ]. However, evidence on mortality for fracture sites other than hip or outcomes for humerus and forearm fractures is less conclusive or lacking at all [ 27 30 ]. Overall, collaborative orthogeriatric care might be beneficial for the treatment of non-hip fragility fractures as well, but as to date, comprehensive evidence is scarce.…”
Section: Introductionmentioning
confidence: 99%